Minimally invasive 1,444-nm Nd:YAG laser treatment for axillary bromhidrosis - Piccolo, Domenico; Mutlag, Mohammed Hussein; Pieri, Laura; Fusco, Irene; Conforti, Claudio; Crisman, Giuliana; Bonan, Paolo (Frontiers in Medicine, 2023)
Background Axillary bromhidrosis is an apocrine glands hyperactivity disease. Methods A total of 24 patients (15 men and 9 women) with axillary bromhidrosis underwent a laser procedure with a 1,444-nm Nd:YAG laser. Parameters evaluated in this study were as follows: the degree of malodor (T0, baseline; T30, after 1 month; and T180, after 6 months), postoperative pain, short-term decreased mobility (T1, after 1 day; T7, after 7 days; and T30, after 1 month), and overall satisfaction (T30, after 1 month and T180, after 6 months). A visual analog scale (VAS), from 0 to 10, was used to assess pain and decreased mobility, with lower values denoting less severity. Results A total of 24 patients were followed up for 6 months after laser treatment. At baseline, all patients (100%) complained of a strong axillary malodor (mean degree of malodor at T0 = 2.0 ± 0.00). It decreased to 0.50 ± 0.64 at T30. At T180, the degree of malodor was 0.54 ± 0.57. Both T30 and T180 degrees of malodor significantly decreased from the baseline value (p < 0.01). The mean degree of patient satisfaction at T30 was 1.75 ± 0.52, and at T180, it was 1.67 ± 0.21. Among the 24 patients, eight complained of moderated pain 1 day after treatment. The pain subsided on day 7, except for two patients, with VAS = 1. Pain and mobility restrictions were in any case resolved within T30. Conclusion Treatment with a 1,444-nm Nd:YAG laser for subdermal interstitial coagulation could be a less invasive and more effective option treatment for axillary bromhidrosis.